Active transport of RB protein from the nucleus to the cytoplasm as one of the development mechanisms of HER2-positive breast cancer - Kowalik, Artur; Kopczyński, Janusz; Wypiórkiewicz, Elżbieta; Góźdź, Stanisław; Meżyk, Ryszard; Siedlecki, Janusz Aleksander (Polish Journal of Pathology, 2013)
HER2-positive breast cancer (HER2+) occurs in approximately 15-20% of all breast cancers. Biologically this cancer subtype is characterized by an aggressive clinical course (often spread to regional lymph nodes at the time of diagnosis), and after successful treatment high risk of recurrence. Deregulation of the cell cycle is the basis for cancer aggressiveness. The RB protein is one of the key regulators of the cell cycle. There are only a few published studies on the expression and localization of RB protein in the cells of HER2-positive breast cancer. The aim of this study was to determine whether there are differences in the expression and localization of RB protein in HER2-positive breast cancers compared to breast cancers showing no expression of HER2. We used 50 tissue samples from HER2 positive breast cancer and 21 tissue samples derived from patients with HER2 negative breast cancer. The RB protein expression was measured by immunohistochemical techniques in tissue microarray format. Cytoplasmic RB expression was observed in 29 out of 50 (58%) HER2 positive breast cancers. In this group only cytoplasmic expression was observed. There was no case with nuclear expression. In contrast, in the HER2-negative breast cancer control group, in no case RB expression was observed in the cytoplasm (0/21, 0%). All 21 samples (100%) showed expression of RB protein in the nucleus (p < 0.0001). We can speculate that lack of expression suggests alternative mechanisms in the development of HER2 positive breast cancer. We hypothesize that HER2 overexpression is in some way associated with active transport of RB protein from the nucleus to the cytoplasm. This may be an indirect mechanism of inactivation of tumor suppressor protein in breast cancer exhibiting overexpression of HER2.